The Role of Law in Protecting Business Entities Injured by Consumers in E-Commerce Transactions: Peranan Hukum dalam Melindungi Pelaku Usaha Yang Dirugikan Konsumen dalam Transaksi E-Commerce - Febriyanti, Ferli (Annual Review of Legal Studies, 2024)
Violations in e-commerce transactions are not only felt by consumers, but sellers as business entities also experience losses due to negligence and bad faith on the part of consumers. This results in neglect and legal uncertainty for business entities. This research examines and investigates legal regulations in protecting business entities injured by consumers in e-commerce transactions. The research employs a normative legal research method with a legislative approach. The study concludes that legal protection for business entities is not yet optimal. Existing regulations tend to provide protection to consumers as vulnerable parties, making it difficult for business entities to obtain their rights when they suffer losses. Legal protection for business entities is often unresolved due to the lack of good faith from consumers. If disputes arise from such transactions, they can be resolved through both repressive and preventive legal protection. Repressive legal resolution can be achieved through litigation and non-litigation methods, emphasizing the importance of the government's role and law enforcement in protecting the rights and legal certainty of business entities in e-commerce transactions.